Depiction of the episode of the story of sixty-four Yoginis - Temples of India Project Team (Jio Institute, 2024)
One of the most well-known stories of the miracles of Jinadatta Suri, the eleventh oval painting (in clockwise order) in the lower/outer circle in the ceiling of the mandapa (pillared hall) depicts this episode of the story of sixty-four yoginis. The story takes place in Ujjain. Once, Jinadatta Suri was amidst a religious discourse when he foresaw that sixty-four yoginis were coming his way to disturb the gathering. The yoginis arrived disguised as laywomen. Jinadatta Suri asked his disciples to spread sixty-four mats for the yoginis, and using his powers, the acharya (those who impart knowledge) glued the yoginis to the mat. This way, the yoginis were compelled to attend the religious discourse and eventually became disciples of Jinadatta Suri. According to Lawrence Babb, this episode depicts the Jain attempt to tame the tantric goddesses. The inscription reads, ‘Shri Jinadatta Suriji 64 joganiya saji.’